Prevalence and pattern of tobacco consumption in urban community: a cross-sectional study in adults of Central India - Tolani, Priyal H.; Wadhva, Sarita K. (International Journal Of Community Medicine And Public Health, 2021)
Background: The emergence of tobacco related diseases is a burgeoning public health problem. Every year, more than 8 million people die from tobacco use worldwide. It is one of the major causes of death and disease in India and accounts for nearly 1.35 million deaths every year. India is also the second largest consumer and producer of tobacco. There is an urgent need to curb tobacco use and reduce the associated morbidities and mortalities. The present study was the first step in the process of generating strategies to control the use of tobacco by estimating the prevalence and pattern of tobacco use in an urban community. Methods: Study was conducted in the field practice area of an urban health training center of a tertiary care hospital. House to house survey was done. Houses were selected by systemic random sampling. All the people above 15 years of age were included in the study, with total subjects interviewed being 590. Results: 371 (62.88%) study subjects were males and 219 (37.19%) were females. The prevalence of tobacco consumption was found to be 34.06%, 28.81% used smokeless form of tobacco and 3.39% were smokers. About 1.86% consumed both forms of tobacco. Conclusions: Prevalence of tobacco consumption particularly of smokeless form was quite high. Identification of high-risk group and their pattern of tobacco consumption is crucial in developing innovative and effective strategies to curb the tobacco epidemic in India.